DIGITAL ART MARKETPLACES AS STRATEGIC INFRASTRUCTURES FOR YOUNG ARTISTS: ECONOMIC TRANSFORMATION, GLOBAL INTEGRATION, AND CREATIVE INDUSTRY DEVELOPMENT IN UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the strategic importance of digital art marketplaces in supporting young artists and transforming the creative economy of Uzbekistan. The research analyzes the digitization of artworks, online art-sales platforms, NFT technologies, virtual galleries, blockchain-based transaction systems, and the integration of national art markets into global digital ecosystems. Particular attention is devoted to the economic, technological, cultural, and institutional dimensions of digital art-platform development. The study applies comparative, analytical, statistical, and systemic approaches to evaluate the impact of digitalization on artistic commercialization, market transparency, professional accessibility, and international cultural integration. Research findings demonstrate that digital art platforms significantly expand market opportunities for young artists, reduce transaction barriers, strengthen copyright protection, and increase the export potential of national creative industries. The article further explores the role of digital infrastructures in democratizing access to art markets, supporting cultural entrepreneurship, and accelerating the transformation of Uzbekistan’s creative economy within the context of global digitalization.